Assessment of serum vitamin D level in children with type 1 diabetes mellitus: A cross-sectional study - Asmaa Saeed Bayan,; Nahla Abd El-Aziz Nosair,; Abeer Mohamed Salamah, (Journal of the Pakistan Medical Association, 2023)
Objectives: To estimate vitamin D levels in children with type 1 diabetes, and to evaluate its role in the pathogenesis and progress of the disease. Method: The cross-sectional study was conducted at the Paediatric Department of Kafrelsheikh University Hospital, Egypt, from November 2019 to August 2021, and comprised children of either gender aged 3-18 years who were either inpatients or visiting the paediatric outpatient clinic. The subjects were enrolled into 3 groups. Those with newly diagnosed type 1 diabetes were in group A, those with established type 1 diabetes were in group B, and healthy children matched for age and gender and randomly selected were in the control group C. Glycated haemoglobin, serum fasting C-peptide, and serum vitamin D levels were evaluated using quantitative colorimetric determination, an automated analyser, and enzyme-linked immunosorbent assay, respectively. Data was analysed using SPSS 25. Results: Of the 80 subjects, 30(37.5%) were in group A; 17(56.7%) boys and 13(43.3%) girls with mean age 7.77±2.95 years. In group B, there were 30(37.5%) subjects; 14(46.7%) boys and 16(53.3%) girls with mean age 9.6±3.62 years. There were 20(25%) subjects in group C; 10(50%) boys and as many girls with mean age 8.38±2.68 years (p>0.05). Glycated haemoglobin, serum fasting C-peptide and serum vitamin D was significantly different between the control group and the treatment groups (p<0.05). Between the treatment groups, group B had better markers than group A (p<0.05). Conclusion: Serum vitamin D deficiency may play a role in the pathogenesis and insulin sensitivity in cases of type 1 diabetes. Keywords: Diabetes mellitus, C-Peptide, Glycated haemoglobin, Colorimetry